PENGELOLAAN PASAR SELODANG KELAPA PASCA RELOKASI OLEH DINAS PERDAGANGAN DAN PERINDUSTRIAN KABUPATEN INDRAGIRI HILIR TAHUN 2022-2024 - Afriansyah, Tedy; ', Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
The management of the people's market aims to form an orderly, safe and comfortable market for the community because the local government as a manager and facilitator manages the people's market in the region, so the creation of a good market is parallel to the management and fulfillment of market facilities and infrastructure carried out so that the survival of the public is fulfilled by providing feedback on regional income. The purpose of this research is to describe the management of Selodang Kelapa Market after relocation by the Trade and Industry Office of Indragiri Hilir Regency in 2022-2024. This research was conducted in Tembilahan, precisely in Tembilahan Kota Village. This research uses a qualitative approach with descriptive methods. In collecting data the author uses interview, observation and documentation techniques. This research uses the theory of government management put forward by Taliziduhu Ndraha, namely government planning, government organization, use of government resources, and government control, and factors that influence market management based on the concept put forward by Steers, namely organizational characteristics, environmental characteristics, worker characteristics, management policies and practices. The results of the study concluded that the management carried out on the Selodang Kelapa Market was not fully optimal because there were still many market facilities that had not been fulfilled, since the relocation in 2021 until now it has not found the right location, with the current location still having temporary status, but in the results of interviews conducted by the Department of Trade and Industry of Indragiri Hilir Regency had an evaluation for future steps, re-planning in 2025 by determining the location and preparing a budget to build a more organized building with supporting facilities so that the market that uses Jalan Yos Sudarso can be moved and reduced so that traders or buyers have decent and conducive facilities. Keywords: Market Management, Relocation, Government Control